Knowing but not doing: Quantifying the research-implementation gap in conservation paleobiology - Groff, Dulcinea V.; McDonough MacKenzie, Caitlin; Pier, Jaleigh Q.; Shaffer, Austin B.; Dietl, Gregory P. (Frontiers in Ecology and Evolution, 2023)
Conservation paleobiology aims to provide a longer-term perspective on environmental problems to inform decisions about natural resource conservation. As such, conservation paleobiology research falls short when geohistorical data and insights do not inform conservation practice, contributing to the well-known idea that a “gap” exists between the production and use of science in the environmental realm. Our study quantified the extent of this research-implementation (or knowing-doing) gap through a systematic literature review and survey questionnaire. We determined whether empirical studies in conservation paleobiology with a link to conservation, management, or restoration documented the use of geohistorical data to implement some form of action or if there was a specific mention of how the geohistorical data could be used in theory. Results indicate that “applied” conservation paleobiology has a poor record of translating research into action. Tangible conservation impacts were evident in only 10.8% of studies. Over half of these studies included coauthors affiliated with a conservation organization. Among the studies coded as having a theoretical application, 25.2% specified how the geohistorical data could be implemented to enhance conservation, management, or restoration actions. All studies documenting action used geohistorical data from the geologically recent past where the species and habitats are familiar to those found today. Drawing insights from the bright spots we identified, we offer some practical suggestions to narrow the gap between knowing and doing in conservation paleobiology.